2004
DOI: 10.1016/j.bbmt.2003.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Development of early neutropenic fever, with or without bacterial infection, is still a significant complication after reduced-intensity stem cell transplantation

Abstract: Little information is available on the clinical characteristics of infectious complications that occur in the early period after reduced-intensity stem cell transplantation (RIST). We retrospectively investigated the clinical features of neutropenic fever and infectious episodes within 30 days after RIST in 76 patients who had received fluoroquinolones as part of their antibacterial prophylaxis. Preparative regimens included cladribine 0.66 mg/kg or fludarabine 180 mg/m2 plus busulfan 8 mg/kg. All but 1 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 22 publications
2
23
0
2
Order By: Relevance
“…[26][27][28][29] RIST seemed to be associated with less infections due to the shorter duration of neutropenia and less damage to mucosal barriers. However, we showed that opportunistic infection is the second leading cause of death in RIST.…”
Section: Discussionmentioning
confidence: 93%
“…[26][27][28][29] RIST seemed to be associated with less infections due to the shorter duration of neutropenia and less damage to mucosal barriers. However, we showed that opportunistic infection is the second leading cause of death in RIST.…”
Section: Discussionmentioning
confidence: 93%
“…[32][33][34][35] Little is known about the clinical usefulness of additional steroid use in CBT. A previous study reported that corticosteroid use was not a significant risk factor for infection in RI-CBT.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to myeloablative regimens, nonmyeloablative conditioning is associated with less myelotoxicity and produces fewer extra-haematological toxicities, in particular less damage to the mucosal barriers of the gastrointestinal tract [9][10][11]24 . However, the relative intensity of these treatments ranges from the reducedintensity conditioning (RIC) regimens that still induce severe neutropenia and are carried out in inpatient protected units 10,15,25,26 , to the truly nonmyeloablative regimen developed by the Seattle team that causes little neutropenia, can be performed as outpatient and cause much less morbidity 9,12,13,24 . Using the Seattle regimen, we indeed encountered virtually no toxic mucositis and no gastrointestinal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not yet clear whether NMSCT would indeed result in a reduced risk of infection compared to standard myeloablative allogeneic transplantation. Available data have sometimes indicated a reduced incidence of infection after NMSCT 9, 10 but other studies have observed similar rates of infection after the two forms of allogeneic transplantation 11,12,[15][16][17][18] . We therefore conducted a retrospective study to describe the incidence and types of infection in 62 recipients of a NMSCT in our institution.…”
Section: Introductionmentioning
confidence: 99%